Analysis of the Effect of Inflation, Interest Rates and Exchange Rates on the Number of Sharia Banking Deposits in Indonesia - Tanto Tanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study tries to ascertain how Indonesia's sharia banking deposits are affected by the BI Rate, FDR, inflation, and exchange rates. The research method is quantitative research, and secondary data is used as the data source. The financial reports of Indonesia's sharia banks make up the study population, and research samples of financial report data from 2013 to 2022 are used. A quantitative approach using several linear regression approaches is applied. Using the EVIEWS version 8 analysis tool, the analytical techniques used are regression equation testing, classical assumption testing, and descriptive analysis. BiRate, FDR, inflation, and exchange rate are the variables considered. The findings of the study indicate that in Indonesia, sharia banking deposits are simultaneously impacted by the interest rate, the foreign exchange rate, inflation, and the Federal Reserve rate. The t-test results show that the exchange rate variable has a significant negative impact on Indonesian sharia banking deposits. This is demonstrated by partial calculations for the t-count, which show that while the exchange rate variable has a negative impact on the quantity of sharia banking deposits in Indonesia, the BI Rate, FDR, and inflation variables have positive impacts.